The effectiveness of augmented reality-based pocket books to improve numeracy literacy skills of elementary school students - Alfi Laila; Saiful Afandi; Mohd Hanafi Mohd Yasin (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
Elementary school students’ numeracy literacy skills remain low, particularly in understanding the concepts of two-dimensional and three-dimensional shapes, due to the limited use of instructional media. This study aims to examine the effectiveness of an augmented reality-based pocket book in improving students’ numeracy literacy. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved 100 students from five elementary schools in Pakel District, using a pretest–posttest design. Data analysis was conducted using the N-Gain test to measure the improvement in students’ skills after utilizing the media. The results revealed an N-Gain score of 0.85, which falls into the high category, indicating a significant improvement in students’ understanding of mathematical concepts through interactive visualization. Thus, the augmented reality-based pocket book is proven to be effective and feasible for broader implementation in elementary numeracy literacy learning.